The Effect of Principal Managerial Skills on Student Discipline: Analysis of Implementation Based on Management Stages - Tuti Syafrianti; Eka Sukmawati (STAI Serdang Lubuk Pakam, 2023)
There are many things that affect student discipline, one of which is the principal's managerial skills. Because disciplinary competence is not only the teacher's mandate, but especially the ability of the principal to do managerial. In this regard, this study aims to determine the influence of the principal's managerial skills on student discipline. The research method used is quantitative by using simple linear regression analysis which is used to obtain the value of the correlation coefficient and also the regression coefficient. The population in this study, the teachers of SMA Negeri 6 Pekanbaru totaling 70 people and the sample amounted to 60 people. From the calculation results of simple linear regression analysis, the regression equation is obtained, namely: Y=-411 + 1.580, so it can be interpreted that one unit of student discipline score will affect the principal's management by 1.580 at a constant -411. From the results of the study it was concluded that there was an influence of the principal's management on student discipline. This is evidenced from the results of the regression analysis obtained tcount of 15.092 > ttable 1.684 with Sig (0.000)<α (0.05). The results of this study have implications for the development of a principal's management model in improving student discipline.